Multivessel spontaneous coronary artery dissection of left and right coronary systems. (24th October 2013) - Asrar ul Haq, Muhammad; Mutha, Vivek; van Gaal, William J
Abstract : Spontaneous coronary artery dissection (SCAD) involving multiple coronary arteries simultaneously is extremely rare. It should be considered in younger patients, especially who do not have traditional cardiac risk factors. We present a case of young male patient presenting with acute coronary syndrome associated with ST segments elevation on ECG following physical stress whose coronary angiography revealed SCAD of the left anterior descending as well as the right coronary artery and discuss the therapeutic options with a brief review of the limited evidence.